Integración de imágenes satelitales sentinel-2 en CDCol (2020)
The Colombian data cube (CDCol) is a tool that enables working and accessing to satellite imagery. Up until now CDCol only accepted the use of Landsat imagery. This document studies the characteristics of sentinel-2 imagery and describes a methodology for including these images into CDCol given its higher temporal and spatial resolutions.